Passerini and Ugi Reactions Involving Kinetically Unstable Isocyanides. Issue 44 (11th October 2021) - Quelhas, Alexandre; Gazzeh, Houda; Roisnel, Thierry; Trolez, Yann; Guillemin, Jean‐Claude
Abstract: Kinetically unstable isocyanides as vinyl, allenyl and propargyl isocyanides react in Passerini and Ugi reactions faster than they decompose and lead to functionalized α‐acyloxy amides and α‐amino amides, respectively, which can subsequently be used in reactions involving the unsaturated substituent. Abstract : The kinetically unstable vinyl, allenyl and propargyl isocyanides were reacted under the conditions of Passerini and Ugi reactions. They led to α‐acyloxy amides and α‐amino amides with an unsaturated substituent on the nitrogen atom in reasonable yields. Some of them were then functionalized thanks to the pending unsaturation, opening the field of complex products in subsequent reactions.